PRESEPTAL CELLULITIS DUE TO IMPETIGO - A CASE REPORT OF UNCOMMON PRESENTATION IN PAKISTAN - Chen, Philumena; Shah, Aleena; Kausar, Ayisha (Journal of Ayub Medical College Abbottabad, 2023)
Preseptal cellulitis is the skin and soft-tissue infection of periorbital region especially common in the pediatric population. There are many risk factors, however in our case report, the patient had impetigo presenting as preseptal cellulitis. We report a case of a 7 year old presented with left upper eyelid swelling which was associated with crusted skin lesions. Patient was treated conservatively with a team of Ophthalmologist and Dermatologist. The patient recovered within 2 weeks. There is lack of documentation that preseptal cellulitis can be because of highly infectious skin diseases, therefore it is important to keep in mind the uncommon causes of preseptal cellulitis. A multidisciplinary care approach is necessary to treat the underlying etiological cause in the management for favorable outcomes.